2007
DOI: 10.1002/jor.20485
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression in endoprosthesis loosening: Chitinase activity for early diagnosis?

Abstract: The aim of the study was to identify markers for the early diagnosis of endoprosthesis loosening, for the differentiation between wear particle-induced and septic loosening and to gather new insights into the pathogenesis of endoprosthesis loosening. Gene expression profiles were generated from five periprosthetic membranes of wear particle-induced and five of infectious (septic) type using Affymetrix HG U133A oligonucleotide microarrays. The results of selected differentially expressed genes were validated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…The timely and accurate diagnosis of periprosthetic infection has an important influence on consequent treatment in aspects of patient morbidity, hospitalization time and costs 5–7 . Various attempts have been made to optimize the pre‐operative diagnostic procedure of infective loosening, 15–17 including time‐consuming and expensive tests, such as fluorodeoxyglucose‐positron emission tomography and immunoscintigraphy 18,19 . In contrast, histopathological examination is comparatively inexpensive and has the additional ability to rule out malignancy and identify the type and amount of wear‐particles in cases of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…The timely and accurate diagnosis of periprosthetic infection has an important influence on consequent treatment in aspects of patient morbidity, hospitalization time and costs 5–7 . Various attempts have been made to optimize the pre‐operative diagnostic procedure of infective loosening, 15–17 including time‐consuming and expensive tests, such as fluorodeoxyglucose‐positron emission tomography and immunoscintigraphy 18,19 . In contrast, histopathological examination is comparatively inexpensive and has the additional ability to rule out malignancy and identify the type and amount of wear‐particles in cases of aseptic loosening.…”
Section: Discussionmentioning
confidence: 99%
“…Unlike the myeloid cell marker CD68, the T‐cell marker CD3 was not present among significantly altered genes. Representing the main result of overall RNA expression profiling in this study, chitinase 1 (CHIT1), or chitotriosidase, was identified as the top altered gene (44‐fold, p = 0.0004) [Figure (B)] and was tested as possible marker for aseptic loosening . Considering that chitin‐degrading chitinases are known modulators of immune responses to chitin‐bearing pathogens, we focused our further analysis of implant‐related immune responses on this ex vivo human study as the most relevant available in silico model that may provide mechanistic insights into the CD68/chitinase co‐expression profile in wear particle‐induced loosening.…”
Section: Resultsmentioning
confidence: 99%
“…This is the first study to demonstrate cell surface and cytoplasmic markers indicative of loosening of THAs by means of multiparameter flow cytometry. Recent studies have reported the implication of several CDs or other markers in the loosening process [22][23][24]. However, these markers were determined from samples obtained from periprosthetic membranes and not from blood samples.…”
Section: Discussionmentioning
confidence: 99%